2021
DOI: 10.1039/d1qo00559f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of polysubstituted azetidines via cascade trifluoromethylation/cyclization of N-allyl ynamides

Abstract: Traditional methods for the transformation of N-allyl ynamides rely on the formation of a ketenimine intermediate or its equivalent, while novel reaction modes remain to be developed. Herein, a cascade...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…In addition to these examples, various trifluoromethylation reactions with subsequent cyclizations of alkenes or alkynes have been reported. [125][126][127][128][129][130][131][132][133][134][135][136] Directed toward the synthesis of products with quaternary asymmetric carbons, the introduction of aryl and trifluoromethyl groups at the double bond of acrylamide compounds was developed by Liu et al [137] In this reaction, acrylamide 70 reacted with reagent 60 and arylboronic acid 71 in the presence of a copper catalyst and a bisoxazoline (Box) ligand bearing two benzyl groups to give α-arylated β-trifluoromethylated products 72 with a quaternary carbon (Scheme 28). Particularly, in the case of acrylamide with an alkyl group at the α-position, the corresponding product can be obtained with high enantioselectivity.…”
Section: Trifluoromethyl-and Trifluoromethylthiobenziodoxolesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to these examples, various trifluoromethylation reactions with subsequent cyclizations of alkenes or alkynes have been reported. [125][126][127][128][129][130][131][132][133][134][135][136] Directed toward the synthesis of products with quaternary asymmetric carbons, the introduction of aryl and trifluoromethyl groups at the double bond of acrylamide compounds was developed by Liu et al [137] In this reaction, acrylamide 70 reacted with reagent 60 and arylboronic acid 71 in the presence of a copper catalyst and a bisoxazoline (Box) ligand bearing two benzyl groups to give α-arylated β-trifluoromethylated products 72 with a quaternary carbon (Scheme 28). Particularly, in the case of acrylamide with an alkyl group at the α-position, the corresponding product can be obtained with high enantioselectivity.…”
Section: Trifluoromethyl-and Trifluoromethylthiobenziodoxolesmentioning
confidence: 99%
“…Trifluoromethyl radical species are expected to be involved in this reaction, and the authors have confirmed by DFT calculations that 5‐ endo cyclization is favored compared to other possible cyclizations pathways. In addition to these examples, various trifluoromethylation reactions with subsequent cyclizations of alkenes or alkynes have been reported [125–136] …”
Section: Trifluoromethyl‐ and Trifluoromethylthiobenziodoxolesmentioning
confidence: 99%
“…In 2021, Zhu and co‐workers reported the construction of polysubstituted azetidine‐fused tricyclic compounds via cascade trifluoromethylation/cyclization of N ‐allyl sulfonyl ynamides (1,5‐enynes) with Togni's reagent II (Scheme 31). [58] This transformation was achieved under Cs 2 CO 3 ‐prompted or visible‐light induced conditions. Mechanistically, the single electron transfer between Cs 2 CO 3 and Togni's reagent II gives trifluoromethyl radical CF 3 ⋅, which adds to the double bond of ene‐ynamide to form alkyl radical 31‐A .…”
Section: Radical Cyclization Of 1n‐enynesmentioning
confidence: 99%
“…Togni reagent's I and II ( 31 , 38 ) have also been widely employed for ⋅CF 3 triggered intramolecular cyclizations (Scheme 44). In 2021, Bai, Yuan, Zhu, and coworkers reported the synthesis of CF 3 ‐containing azetidines by employing 31 and an organophotocatalyst [160] . Notably, the 4‐ exo‐dig radical cyclization represents a rare reaction motif and is postulated to occur through an alkenyl radical upon ⋅CF 3 addition.…”
Section: Trifluoromethylation (Cf3)mentioning
confidence: 99%